Collaborative Governance in Stunting Reduction: A Case Study in Banyumas District - Anggara Setya Saputra; Denok Kurniasih (Universitas Sultan Ageng Tirtayasa, 2023)
This study discusses collaborative governance in an effort to accelerate stunting reduction in Banyumas Regency. The problem of stunting is currently a problem faced by the government at the local government level to the central government. Banyumas Regency is one of the regencies that has a commitment to tackling and accelerating the current stunting reduction. The purpose of this research is to see how the collaborative process is carried out between local governments, community groups, and the private sector in collaborating and synergizing to overcome and reduce stunting rates. This study looks at how each party plays a role and is responsible for each other which is contained in a common commitment. This study uses descriptive qualitative research methods, with a case study approach, data analysis techniques using triangulation of data and sources, while informants are selected based on ability in accordance with purposive sampling rules. The results of this study are divided into several aspects which include the initial conditions in the collaborative governance process by looking at the situation and condition of stunting in Banyumas Regency. Aspects of leadership and communication forums that are netted in the community starting from the village government level, sub-district, to the district level. The forum used for coordination is through posyandu groups that have been scattered in each village. The results of this collaborative governance process were able to run well, so that gradually the government was able to reduce stunting rates and develop a health education network model in an effort to prevent and accelerate stunting reduction in Banyumas Regency.